Potential demand and supply of beef cattle in Indonesia - Astiti, Ni Made Ayu Gemuh Rasa; Wedaningsih, Komang Nita; Parwata, I Kadek Wira (Eximia, 2023)
This research is a literature study on the demand and supply of beef in Indonesia. This study aims to determine the demand and supply and stock of beef in Indonesia. The method used in this study is qualitative research using field research techniques, namely direct observation of the object under study in order to obtain relevant data. The data used in this research are primary data and secondary data. The results of the study concluded that beef cattle are the largest meat contributor from the ruminant group to national meat production so that this livestock business has the potential to be developed as a profitable business. The increase in population and public awareness of consuming highly nutritious protein has made the demand for beef tend to increase from year to year. However, the fact is that beef production in Indonesia has not been able to meet public demand or consumption. Various efforts have been made by the government to maximize and increase beef production, but in reality these efforts have not been successful, so the government imports to meet domestic needs.